2012
DOI: 10.1039/c2ra21937a
|View full text |Cite
|
Sign up to set email alerts
|

π–π and cation–π interactions in protein–porphyrin complex crystal structures

Abstract: In this study we have described the p-p and cation-p interactions between the porphyrin ring and the protein part of porphyrin-containing proteins to better understand their stabilizing role. The number of pp interactions was higher than that of cation-p interactions in the same set of proteins studied. The pyrrole groups of one porphyrin can be involved in p-p interactions with p systems of another porphyrin in the protein. We have found 5.1% cation-p interactions between porphyrin Fe 2+ metal cations and p s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…There is no significant statistical difference in the  angle distribution between the multiple and the single amide- interactions. The preferred orientations are quite similar to those found in aromatic-aromatic interactions, 47 and T-shaped orientation is observed. In the parallel-stacked case, van der Waals contribution is the dominant effect and the electrostatics contribution is actually repulsive, although small in value (<1 kcal mol -1 ).…”
Section: Interaction Geometries and Energetic Contribution Of Amide-π Interactionssupporting
confidence: 79%
“…There is no significant statistical difference in the  angle distribution between the multiple and the single amide- interactions. The preferred orientations are quite similar to those found in aromatic-aromatic interactions, 47 and T-shaped orientation is observed. In the parallel-stacked case, van der Waals contribution is the dominant effect and the electrostatics contribution is actually repulsive, although small in value (<1 kcal mol -1 ).…”
Section: Interaction Geometries and Energetic Contribution Of Amide-π Interactionssupporting
confidence: 79%
“…Although aromatic interactions are often grouped together, several distinct types are observed, each with their own characteristic stabilities: sandwiched, parallel displaced, T-shaped, edge-to-face; cation-π interactions also represent stabilizing interactions found in proteins ( Figure 5). 85,86,87,88,89,90,91,92…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5: Illustration of stabilizing aromatic (π-π, cation-π) interactions with their corresponding estimated stabilization energies. 85,89,87,86,90,91,92 It should be noted that all of the π-π interaction energies shown here were calculated in the gas phase, while the cation-π term was calculated in solution: Commonly seen ring-ring centroid distances between aromatic residues in such clusters are between 5-8Å. 84 Furthermore, they concluded that aromatic substrates should preferentially bind in protein active sites with significant aromatic character.…”
Section: + a ) C ) D ) E ) B )mentioning
confidence: 89%
“…9,20 Generally the composition of cation- interaction forming residues is similar to other globular proteins. [39][40][41][42] The organization of multicomponent supramolecular assemblies is often governed by multiple noncovalent interactions. 43 Ternary complexes are the…”
Section: Preference Of Cationic and Aromatic Residues For Forming Cat...mentioning
confidence: 99%